P132 Review of smoking, alcohol and drug use within an inner-city integrated GUM service. (30th June 2016) - Cochrane, Sarah; Boylan, Johnny; Wheeler, Helen; Horner, Paddy
Abstract : Background/introduction: Evidence suggests alcohol and drug use correspond to poorer sexual health outcomes. NICE recommend routine screening for alcohol use disorders, with adults and young people regularly attending GUM services identified as a high risk group. Assessment for drug and alcohol misuse enables health promotion through brief intervention. Aim(s)/objectives: To assess the prevalence of cigarette, alcohol and drug use within our GUM clinic population. Methods: Patients were requested to complete a questionnaire as part of the clinic triage form, including data on smoking status, alcohol use using AUDIT-C and recreational drug use. Cases were randomly selected for retrospective review over two week-long periods in June-July 2015. Results: 493 patients were reviewed: 261 (52.9%) female vs 232 (47.1%) male. Ages ranged from 14–79 (median = 28). 27.9% were current smokers (F = 26.8%, M = 29.2%). 391 (79.3%) patients completed questions to allow adequate assessment of their alcohol use. 220 (56.3%) scored ≥5 using the AUDIT-C screening tool, indicating need for further discussion. 317/409 (77.5%) disclosed binge drinking. Of the 418 patients (84.8%) who responded, 73 (17.5%) admitted recreational drug use. The most common method of use disclosed was smoking (71.2%), followed by snorting (49.3%) and pills (30.1%). (31 reported more than 1 method.) Discussion/conclusion: Over half of patients attending our clinic warranted further assessment or brief intervention regarding their alcohol use. Recreational drug use and smoking was higher than that of the general population. Further staff training and developing links with local support services will improve the holistic management of our patients.